2016
DOI: 10.1021/acs.iecr.6b00529
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Extended Kalman Filtering for Wastewater Treatment Processes

Abstract: A wastewater treatment plant is a large-scale nonlinear system including a series of biological reactors and a settler. In this work, we propose a distributed state estimation scheme for wastewater treatment processes in the context of extended Kalman filtering. Specifically, we consider a wastewater treatment process that includes a fivecompartment reactor and an ideal splitter. First, we present a method to design the sensor network for the process and then discuss how the process may be decomposed into subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…In [8,26,27,28], distributed data fusion was introduced on the basis of EKF to solve different projects. However, how the EKF uses the first-order Taylor expansion to linearize the system yields the error of the high-order part.…”
Section: Algorithm Descriptionmentioning
confidence: 99%
“…In [8,26,27,28], distributed data fusion was introduced on the basis of EKF to solve different projects. However, how the EKF uses the first-order Taylor expansion to linearize the system yields the error of the high-order part.…”
Section: Algorithm Descriptionmentioning
confidence: 99%
“…In a distributed control system, a distributed state estimation scheme is preferred from a fault tolerance perspective. In the study of distributed state estimation, there are many distributed Kalman filtering research results [7,8]. These methods are mainly based on the consensus algorithm and have great limitation for nonlinear systems [9].…”
Section: Introductionmentioning
confidence: 99%
“…Communication with a remote control centre and the associated delays also make central estimation unattractive compared to its distributed counterparts. It has indeed been shown that distributed estimation is more accurate than central estimation in the case of communication under poor weather conditions [1]. These disadvantages of cen-tral estimation provide a compelling need for distributed estimation schemes.…”
Section: Introductionmentioning
confidence: 99%